Choosing change strategy for ISO/IEC 33014. Issue 8 (1st July 2015) - Pries‐Heje, Jan; Johansen, Jørn; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
Abstract The ISO/IEC 33014.2013 1 standard on process improvement includes a core activity called 'identify the overall change strategy', which includes selecting a change strategy among the many available. This selection can be carried out using the ImprovAbility model 2 in which there is a framework of how to select change strategy. The framework contains 10 different change strategies to choose from. But which ones are chosen in practice? To answer that, we have analyzed data from 134 assessments in 129 organizations that have used the framework. We give a ranking of strategies chosen, and we analyze how they adapt the change strategy to their specific conditions. We conclude that the most often recommended organizational change strategy is optionality followed by three other strategies: specialist‐driven, production‐organized, and learning‐driven. Copyright © 2015 John Wiley & Sons, Ltd.